The Urgency of Women's Education to Face the Era of Society 5.0 According to the Islamic Perspective - Bela Noviana Dewi; Mufidah Ch; Laily Hafidzah (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2022)
The world of education is still not very sensitive to the emergence of gender inequality for students, especially discrimination against women. The purpose of this study is to describe how important women's education is from an Islamic perspective, especially in the context of welcoming the era of society 5.0 which is marked by increasingly advanced technological developments. In this era, humans are required to continue to innovate in various aspects of life. The research method used is the descriptive qualitative method. The result of this research is Islamic view that all human beings have the right to get proper education, including women who will be the first